Application of 3D-Printed Orthopedic Cast for the Treatment of Forearm Fractures: Finite Element Analysis and Comparative Clinical Assessment. (26th July 2020) - Chen, Yanjun; Lin, Hui; Yu, Qinqin; Zhang, Xiaodong; Wang, Defeng; Shi, Lin; Huang, Wenhua; Zhong, Shizhen
Abstract : Objective . This pilot study is aimed at investigating the mechanical characteristics of a cast-wrapped fractured forearm and performing a clinical comparative study of our own developed 3D-printed orthopedic cast. Methods . An integrated finite element (FE) model including a forearm and a 3D-printed cast wrapping the forearm was created. The distal radial ulna in this model was cut through to mimic the bone fracture. A 400 N force and 1 Nm rotation moment, which were much larger than the loading conditions encountered in daily life for a human being, were applied on the palm. We conducted a comparative clinical study by using statistical assessment. 60 patients with forearm fractures were selected and treated with manual reduction and external fixation cast. All patients were divided into three groups with equal members (20): (a) 3D-printed external cast group, (b) traditional plaster external fixation group, and (c) splint external fixation group. The clinical efficacy, wrist function, and patient satisfaction were scored and compared. Results . In the condition of 400 N loading, the fracture displacements in anterior-posterior (AP), posterior-anterior (PA), medial to lateral (ML), and lateral to medial (LM) compression directions were 1.2648, 1.3253, 0.8503, and 0.8957 (mm), respectively, and the corresponding fracture stresses were 4.5986, 3.9129, and 5.0334, 7.9197 (MPa), respectively. In the inward (IR) and outward (OR) rotations, the fracture displacements were both 0.02628 (mm), and the corresponding fracture surface stresses were 0.1733 and 0.1723 (MPa), respectively. In the clinical efficacy, wrist function, and patient comfort evaluation, the total scores of group A were both higher than those in groups B and C (P < 0.05 ). Conclusion . A 3D-printed orthopedic cast was capable of exerting appropriate mechanical correction loads on specific areas to maintain optimal alignment of a fractured forearm and thus could achieve the favorable clinical efficacy and patient comfort.